PENGARUH PELATIHAN DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN “KSP PONDOK SARI” - I Ketut Sudana; Ni Luh Putu Yesy Anggreni; Putu Siti Firmani (Universitas Mahendradatta Denpasar, 2024)
A cooperative is an organization formed on the basis of common interests. We can see whether a cooperative is healthy or unhealthy from the performance of its management and employees. In order to increase the competency of cooperative employees, training is needed that can increase competency. So that the management and employees in the cooperative become competent in their fields. Apart from that, communication between leaders, employees and customers is something that cannot be separated. To obtain good work productivity, of course communication must be established well, so that the work atmosphere becomes comfortable.The research entitled